Prediction of Parturition in Canine Using Serial Ultrasound Foetal Monitoring and Serum Progesterone Levels - Gupta, Falguni; Dagli, Nilesh; Gulavane, Sarita; Chaudhari, Ravindra; Gaikwad , Sandeep (The Indian Journal of Animal Reproduction, 2025)
A 2-year-old Himalayan Sheepdog with unclear mating history was presented with concerns of delayed parturition. Diagnostic procedures used were serial serum progesterone analysis and ultrasonography to determine approximate gestational age and foetal viability. Data collection of the same parameters were done 48 hrs apart. Owner was advised to monitor rectal temperature and wait for natural whelping after drop in progesterone levels. On first ultrasound scan bi-parietal diameter (BPD) and foetal heart rate were 2.62cm and 244 bpm, respectively. The corresponding serum progesterone was 3.15ng/ml. The readings pertaining to bi-parietal diameter (BPD) and foetal heart rate 48 hours after first clinical examinations were 2.76 cm and 236 bpm, respectively, whereas the serum progesterone was 0.76 ng/ml. Eventually the bitch delivered eight healthy puppies naturally after 14 hrs of last sample collection.